1993
DOI: 10.1111/j.2042-3306.1993.tb02927.x
|View full text |Cite
|
Sign up to set email alerts
|

Administration of a receptor antagonist for platelet‐activating factor during equine endotoxaemia

Abstract: Summary Platelet‐activating factor (PAF) is an important mediator of endotoxaemia and various PAF receptor antagonists prevent many of the adverse effects of experimental endotoxaemia in laboratory animals. In this study a specific PAF receptor antagonist was used to investigate the role of PAF in equine endotoxaemia. At an interval of not greater than 10 days, 6 horses were each challenged with endotoxin and endotoxin with concurrent administration of SRI 63–441, a PAF receptor antagonist. The order of the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“… 20 Although that study involved a potent and selective PAF antagonist (CV3988), it did not control for fluctuations in T a , which might have affected the results. To complicate the matter even further, there is evidence against the involvement of the PAF receptor in the T b responses to LPS, at least when it comes to fever, as LPS fever was only marginally affected by a PAF antagonist in a study in horses 21 and not affected at all by another PAF antagonist in a study in humans. 22 …”
Section: Introductionmentioning
confidence: 99%
“… 20 Although that study involved a potent and selective PAF antagonist (CV3988), it did not control for fluctuations in T a , which might have affected the results. To complicate the matter even further, there is evidence against the involvement of the PAF receptor in the T b responses to LPS, at least when it comes to fever, as LPS fever was only marginally affected by a PAF antagonist in a study in horses 21 and not affected at all by another PAF antagonist in a study in humans. 22 …”
Section: Introductionmentioning
confidence: 99%
“…There is much evidence to suggest that PAF is a key mediator of endotoxaemia in all species (Rabinovici et al 1991), including the horse (Carrick et al 1993;Evans 1994, 1996). PAF is also a particularly potent stimulus of equine platelet aggregation (Meyers et al 1979;Wimberly et al 1985;Dillon and Heath 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Platelet activation by PAF released from activated leucocytes has been demonstrated by Nguyen et al (1995). Inhibitor studies have shown that PAF receptors are involved in experimental equine endotoxaemia (Carrick et al 1993) and more specifically in the leukocytedependent equine platelet aggregation induced in vitro by LPS Evans 1994, 1996). The ability of dextran-70 to inhibit responses of equine platelets to PAF is probably an important component of its beneficial effect as an antithrombotic in colic cases.…”
Section: Discussionmentioning
confidence: 99%
“…The fourth method of treating endotoxaemic horses is by interfering with the effects of the pro-inflammatory mediators. There have been 3 such approaches evaluated as potential treatments for endotoxaemia in horses, namely administration of PAF receptor antagonists (King and Gerring 1990;Carrick et al 1993), alpha-2 adrenergic receptor antagonists (Eades and Moore 1993) and monoclonal antibodies directed against equine tumour necrosis factor (Cargile et al 1995a,b;Barton et al 1998). Although none of these approaches prevented all of the effects of endotoxin, promising results were obtained with each as both the platelet activating factor receptor antagonist and the alpha-2 antagonist prevented the effects of endotoxaemia on intestinal motility; the antibodies against TNF significantly reduced many of the clinical and laboratory findings associated with endotoxaemia in one study.…”
Section: Interfering With Effects Of Mediatorsmentioning
confidence: 99%